2013
DOI: 10.1155/2013/769594
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Combination Effects of Ethanolic Extract of Ziziphus mucronata Willd. subsp. mucronata Willd. and Antibiotics against Clinically Important Bacteria

Abstract: A pragmatic approach to the treatment of infectious diseases with multicausal agents and prevention of the development of resistant isolates is the combination of herbal remedies with the first-line antimicrobial agents to which most of them have become resistant. This study evaluated the interactions between the ethanolic bark extract of Ziziphus mucronata with known antimicrobial agents in vitro. In this study, the results showed that varied zones of inhibitions (ZME—chloramphenicol (17–42 mm), ZME—amoxicill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
1
10
1
Order By: Relevance
“…The percentage for plant extract inhibition was not calculated as there was no observable microbial growth comparing the test and control wells. The results observed contradict the findings by Olajuyigbe and Afolayan [26]. The bacterial isolates (E. faecalis, E. coli, K. pneumoniae) exhibited varied degree of susceptibility with zones of inhibition ranging between 17 and 27 ± 1.0 mm, though the difference in results can be attributed to the extraction solvent they used.…”
Section: Discussioncontrasting
confidence: 79%
“…The percentage for plant extract inhibition was not calculated as there was no observable microbial growth comparing the test and control wells. The results observed contradict the findings by Olajuyigbe and Afolayan [26]. The bacterial isolates (E. faecalis, E. coli, K. pneumoniae) exhibited varied degree of susceptibility with zones of inhibition ranging between 17 and 27 ± 1.0 mm, though the difference in results can be attributed to the extraction solvent they used.…”
Section: Discussioncontrasting
confidence: 79%
“…With this increased incidence of antimicrobial resistance and appearance of new infectious for their antimicrobial activity and resistance modifying ability (Gibbon, 2004;Coutinho et al, 2009). While the natural products are known to play significant roles in the development of novel drugs and served as leads for the treatment and prevention of diseases (Belini et al, 2008), plant-derived antimicrobials provide the much needed therapeutics (Olajuyigbe and Afolayan, 2013) . The leaves of C. indica showed antimicrobial activity (Abdullah et al, 2012), analgesic activity, and the rhizomes showed a good anthelmintic activity against Pheritima posthuma (Nirmal et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…With the increase in the prevalence of multidrug resistant wound pathogens, synergism testing using various combinations of plant compound and their corresponding synthetic derivatives with antimicrobial drugs could be a more powerful tool in helping to select appropriate antimicrobial therapy to control pathogens. [51][52][53] The indiscriminate use of various antibiotics in the treatment of bacterial infections especially against wound pathogens has led to the emergence and spread of resistant bacterial strains, and this in turn resulted in a great loss of clinical efficacy of previously effective first-generation antibiotics which results in shifting of antimicrobial treatment regimen to second-generation or third-generation antibiotics that are often more expensive with many unwanted side effects to human beings. 54 In fact, studies have shown that crude extracts of plants possess the ability to enhance the activity of antimicrobial agents without causing any unwanted side effects.…”
Section: Discussionmentioning
confidence: 99%